2013
DOI: 10.1186/1476-0711-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multidimensional infection control approach on central line-associated bloodstream infections rates in adult intensive care units of 8 cities of Turkey: findings of the International Nosocomial Infection Control Consortium (INICC)

Abstract: BackgroundCentral line-associated bloodstream infections (CLABs) have long been associated with excess lengths of stay, increased hospital costs and mortality attributable to them. Different studies from developed countries have shown that practice bundles reduce the incidence of CLAB in intensive care units. However, the impact of the bundle strategy has not been systematically analyzed in the adult intensive care unit (ICU) setting in developing countries, such as Turkey. The aim of this study is to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 35 publications
(59 reference statements)
2
28
0
Order By: Relevance
“…Similar to the present study, most of the studies found VAP as the most frequent NIs (4,7,12,13,20) and other studies reported analogous rates of NIs in Argentina and Latin American countries (5, 7). Although some studies detected that UTI was the most prevalent NIs (11,21), it is considerable that researches distinguished higher prevalence of NIs in university hospitals (20,22).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to the present study, most of the studies found VAP as the most frequent NIs (4,7,12,13,20) and other studies reported analogous rates of NIs in Argentina and Latin American countries (5, 7). Although some studies detected that UTI was the most prevalent NIs (11,21), it is considerable that researches distinguished higher prevalence of NIs in university hospitals (20,22).…”
Section: Discussionsupporting
confidence: 90%
“…NIs are associated with considerable morbidity, extra cost, and are responsible for more mortality (9)(10)(11)(12)(13). On the basis of data from death certificates, these infections are the 10th leading cause of death in the United States (5,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Within the scope of other studies addressing the burden of CLABSIs in India, the CLABSI rate in our 3WSC group was similar to the rate of 7.92 CLABSIs per 1000 CL-days found in a 2007 study. 3 In previous studies performed by INICC member hospitals, it was shown that the implementation of a 6-component multidimensional approach for CLABSI resulted in significant reductions in CLABSI rates in Argentina (45.9 vs 11.1 CLABSIs per 1000 CL-days), 13 in Mexico (46.3 vs 19.5 CLABSIs per 1000 CL-days), 12 in Turkey (22.7 vs 12.0 CLABSIs per 1000 CL-days), 9 in India (6.4 vs 3.9 CLABSIs per 1000 CL-days), 8 11 However, in none of the previous studies conducted by INICC the CLABSI rate was lower than 5.2 CLABSIs per 1000 CL-days, as was achieved in the SS þ SUF group. [8][9][10][11][12][13][14] This finding is consistent with the fact that according to the INICC, between 88% and 94% of hospitals in the developing world use 3WSC devices instead of SS þ SUF devices.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 However, to date only 2 studies addressing this issue have been published, which showed higher CLABSI rates in pediatric ICUs in lower-middle-income countries compared with upper-middle-income countries, 6 and significantly higher CLABSI rates in neonatal ICU patients from low-income countries than in lower-middle or upper-middle-income countries. 7 In the developing countries, including India, 8 it has been demonstrated that CLABSI rates can be reduced by more than 50% [8][9][10][11][12][13][14] by adopting a multidimensional approach with the simultaneous implementation of 6 elements: (1) a bundle of interventions, (2) education, (3) outcome surveillance, (4) process surveillance, (5) feedback on CLABSI rates and consequences, and (6) performance feedback.…”
mentioning
confidence: 99%